2021
DOI: 10.1186/s40902-021-00298-3
|View full text |Cite
|
Sign up to set email alerts
|

Nasal sill augmentation: an overlooked concept in rhinoplasty—a technical note and review of the literatures

Abstract: Background Nasal sill is one of the components of the alar ring, affecting the esthetic outcomes of rhinoplasty; accordingly, we developed a novel technique to adjust defects in this area and compared it with the available techniques. Methods Our technique was based on creating a tunnel access to the nasal sill area through an incision made in the lower third of the columella using the open approach or through a nostril base incision in patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Adham et al 16 published their article related to the augmentation of nasal sill defects. The technique they proposed may be particularly useful in patients with cleft lip.…”
Section: Discussionmentioning
confidence: 99%
“…Adham et al 16 published their article related to the augmentation of nasal sill defects. The technique they proposed may be particularly useful in patients with cleft lip.…”
Section: Discussionmentioning
confidence: 99%
“…The alar bases have important roles in terms of overall appearance of the nose and the functionality3 but the research so far which focused specifically on alar base surgery can be considered as insufficient 4. However, it has been reported that alar base was manipulated between the ranges of 15% and 90% during rhinoplasty surgeries 5…”
mentioning
confidence: 99%